IMPLEMENTASI PENDIDIKAN ROHANI DALAM PENINGKATAN MENTAL SPIRITUAL SANTRI DI PONDOK PESANTREN KALIMASADA BANGSRI PLANDAAN JOMBANG - Fadhilah, Ani Nur; Surur, Shobihus (EL-Islam, 2024)
Islamic spiritual education is utilized in various educational settings, such as in Islamic boarding schools (pondok pesantren). The role of Islamic spiritual education is crucial in the process of enhancing the mental and spiritual development of students (santri). Islamic spiritual education is a holistic process that involves both physical and spiritual aspects comprehensively. The process aims to provide comprehensive guidance and care for an individual's physical and spiritual well-being. This research aims to describe the aspects of spiritual and mental development and the implementation of Islamic spiritual education in enhancing the mental and spiritual growth of students at Kalimasada Bangsri Plandaan Islamic Boarding School in Jombang. This research is a qualitative study conducted at Kalimasada Islamic Boarding School in Plandaan, Jombang. Data was collected through observation, interviews, and documentation. Data analysis prioritized relevant information and was presented in a descriptive-analytical format. The conclusions were drawn descriptively. The results of this research show that the teaching of spiritual education at Kalimasada Plandaan Islamic Boarding School is conducted through providing tausiyah (spiritual talks) and spiritual guidance to the students, incorporating religious materials in learning activities, and guiding students to engage in collective worship activities such as congregational prayers, daily Quran recitation (one day one juz), group dhikr (remembrance of Allah), daily rituals, and night prayers. The mental and spiritual well-being of the students at Kalimasada Islamic Boarding School still require regular reminders and guidance to develop into individuals with perfect spiritual character. Regarding the implementation of spiritual education for students at Kalimasada Bangsri Plandaan Islamic Boarding School, it is carried out excellently and has successfully enhanced the students' mental and spiritual growth.